Analisis Faktor-Faktor Kinerja Keuangan Yang Mempengaruhi Harga Saham Dimasa Pandemi Covid-19: Studi Empiris Pada Perusahaan Sektor Manufaktur Yang Terdaftar Di BEI Periode 2020-2022 - Siburian, Martupa J. S; Simanjuntak, Aaron M. A.; Sesa, Pascalina V. S (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
The Covid-19 pandemic has had long, medium-, and short-term impacts on the manufacturing sector listed on the Indonesia Stock Exchange. Pressure on the manufacturing sector was caused by policies made by the government by violating PSBB and policies issued by companies, namely laying off their employees, which impacted decreasing company production. This certainly affects the share price of companies in the manufacturing sector on the Indonesia Stock Exchange (IDX). The purpose of this study is to determine whether Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Debt to Equity (DER) have an effect. The population in this study were all manufacturing companies listed on the IDX for the 2020-2022 period, totaling 181 companies; 52 companies were obtained using purposive sampling. The analytical method used is multiple linear regression analysis with the help of SPSS 29 software. The results of this study indicate that Net Profit Margin, Earning Per Share, and Equity Ratio have a significant effect on stock prices. At the same time, Return On Assets and Return On Equity are not significant on stock prices. The stock price is significantly influenced by the following factors at the same time: Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), Earnings Per Share (EPS), and Debt To Equity Ratio (DER). Keywords: NPM, ROA, ROE, EPS, DER, Stock Price.